Customer Loyalty in Supply Chain Management Model: Promotion, Products, and Registration Decision Analysis - Richardo Richardo; Madya Datuk Muhammad Hussin; Ts. Muhammad Helmi Bin Norman; Hapzi Ali (International Journal of Supply Chain Management, 2020)
Abstract— ASEAN Economic Community (AEC) at the end of 2015 became a new chapter for Indonesia. Customer Loyalty and Supply Chain Management is the result of years of work by the authors on different projects concerning the overlapping areas of supply chains, logistics and marketing, drawing a connection between the literatures to provide a holistic picture of the customer loyalty framework. It is solely to improve the competitiveness of local human resources with foreign workers, especially from ASEAN. In line with that began to emerge places of English training or commonly called tutoring both in rural and urban areas. While the variables used are promotion and price, the decision to register as a mediating variable and customer loyalty based on supply chain management model. The analytical tool used is SEM PLS. Promotion has no positive and significant effect, but price has a positive and significant effect on customer loyalty based on supply chain management model. While other findings are the decision of customers also has a positive and significant effect on customer loyalty based on supply chain management model.